Resilience of farmer-processor relationships to adverse shocks: the case of dairy sector in Poland. Issue 10 (5th October 2015) - Stefano Pascucci, Dr Liesbeth Dries, Professor Konstantinos Karantininis and Professor Gaetano Martino, Dr; Falkowski, Jan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Recent literature has considerably improved our understanding of vertical relations in the food chain. One area which has received relatively little attention however relates to the resilience of an agro-food supply chain, that is its ability to face and, if needed, to recover after a major disruption. The purpose of this paper is to study what factors, including characteristics of vertical links between upstream and downstream sectors, may make farmer-processor relationships more or less resilient to adverse shocks. Design/methodology/approach – To do so, the author uses a unique region-level data set on disruptions to dairy supply chain in Poland during the transition from a centrally planned economy to a market economy. More specifically, using between-region variation, the author investigates why in some regions supply chain disruptions, measured as the breakdown of relationships between farmers and processing industry, were smaller than in other regions. Findings – The findings suggest that the supply chain which the author analysed was less resilient to crisis, i.e. the author observed larger disruptions to supply relations, when the supply base was more fragmented and when farmers had better outside options to market their produce via direct sales to consumers. In addition, dairy supply chain in Poland seemed to be less resilient in regions with larger share of the state-owned land. Research limitations/implications – The results come with several caveats. First, the empirical evidence comes from Poland during the specific period and thus it may not be easily generalised. Second, the results are based on historical correlations. Therefore, although they are robust across various specifications which the author estimates, they may not establish causal relationship due to some omitted variables or potential endogeneity issue. Finally, what the author uses here are region-level data. One may argue therefore that farm-level data would give more fine-tuned focus for testing impacts and theories regarding supply chain resilience. Originality/value – To the best of the author's knowledge, this paper is the first to provide some evidence on agro-food supply chain from this perspective.